Triple Stimulation Technique in Amyotrophic Lateral Sclerosis. Issue 2 (March 2019) - Wang, Yue; Wang, Han; Cui, Li-Ying
Abstract : Purpose: To identify upper motor neuron (UMN) dysfunction using the triple stimulation technique (TST) in amyotrophic lateral sclerosis (ALS). Methods: Fifty ALS and 42 non-ALS patients were examined clinically, using conventional transcranial magnetic stimulation and TST. Results: For ALS patients presenting with UMN in tested limb, the TST amplitude ratio was abnormal in 25 of 28 patients (89.3%). For ALS patients without UMN signs, 6 of 22 patients (27.3%) had an abnormal TST ratio. When clinical signs were not present, both abnormal resting motor threshold and TST indicated a UMN involvement. In non-ALS patients with central motor conduction disorders, the percentage of patients with an abnormal TST was higher for those presenting with clinical UMN signs (9/12, 75.0%) than for those without these signs (1/8, 12.5%). Conclusions: Triple stimulation technique appears to be an accurate, early measure for detecting clinical and subclinical UMN abnormalities in ALS. Triple stimulation technique could also be useful to investigate central motor conduction abnormalities in other disorders.